Genetic Diversity, Antimicrobial Susceptibility, and Biofilm Formation of Cronobacter spp. Recovered from Spices and Cereals - Li, Yuanhong; Yu, Huan; Jiang, Hua; Jiao, Yang; Zhang, Yaodong; Shao, Jihong (Frontiers in Microbiology, 2017)
Cronobacter species are important food-borne opportunistic pathogens which have been implicated in the cause of necrotizing enterocolitis, sepsis, and meningitis in neonates and infants. However, these bacteria are routinely found in foodstuffs, clinical specimens and environmental samples. This study investigated the genetic diversity, antimicrobial susceptibility and biofilm formation of Cronobacter isolates (n=40) recovered from spices and cereals in China during 2014-2015. Based on the fusA sequencing analysis, we found that the majority (23/40, 57.5%) of Cronobacter isolates in spices and cereals were C. sakazakii, while the remaining strains were C. dublinensis (6/40, 15.0%), C. malonaticus (5/40, 12.5%), C. turicensis (4/40, 10.0%), and C. universalis (2/40, 5.0%). Multilocus sequence typing (MLST) analysis produced 30 sequence types (STs) among the 40 Cronobacter isolates, with 5 STs (ST4, ST13, ST50, ST129, and ST158) related to neonatal meningitis. The pattern of the overall ST distribution was diverse; in particular, it was revealed that ST148 was the predominant ST, presenting 12.5% within the whole population. MLST assigned 12 isolates to 7 different clonal complexes (CCs), 4, 13, 16, 17, 72, 129, and 143, respectively. The results of O-antigen serotyping indicated that C. sakazakii serotype O1 and O2 were the most two prevalent serotypes. The antimicrobial susceptibility testing showed that the 40 Cronobacter isolates were susceptible to most of the antibiotics tested except for ceftriaxone, meropenem and aztreona. Of the 40 Cronobacter strains tested, 13 (32.5%) were assessed as weak bioflim producers, one (2.5%) was a moderate biofilm producer, one (2.5%) was strong biofilm producer and the others (62.5%) were non-biofilm producers. MLST and O-antigen serotyping have indicated that Cronobacter strains recovered from spices and cereals were genetically diverse. Isolates of clinical origin, particularly the C. sakazakii ST4 neonatal meningitic pathovar, have been identified from spices and cereals. Moreover, antimicrobial resistance of Cronobacter strains was observed, which may imply a potential public health risk. Therefore, the surveillance of Cronobacter spp. in spices and cereals should be strengthened to improve epidemiological understandings of Cronobacter infections.